Intencionalidade, experiência banal e comunicação: esboço de prospecção fenomenológica do cotidiano - CASTRO, Fábio Fonseca de (Universidade Estadual do Rio de Janeiro, 2022)
The article proposes a phenomenological exploration of the notion of daily life, understanding it as living experience, as opposed to experience, from the philosophical debate about the world of life (Lebenswelt). The purpose of this survey is to think about the nature of communicative experience in everyday life. In this task, we dialogue with Heidegger’s concept of iddle talk (Gerede), trying to understand how intersubjectivity is produced in contemporary culture.